The Role of Bank Syariah Indonesia Microfinance in Financing Small-Scale Businesses - Iqbal, Adi; Subhan, Muhammad (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2022)
This study aims to determine the role of microfinance on the business of MSME customers at Bank Syariah Indonesia at the Sarolangun Branch Office. This is field research with descriptive qualitative in nature. Sources of data used are primary and secondary data sources. Data was collected using interview and documentation techniques. The data from the findings are described descriptively and analyzed using inductive thinking. The results of this study also concluded that the role of micro-financing at Bank Syariah Indonesia Sarolangun Branch Office in MSME business has less effect on increasing customer business income, this can be proven by the absence of an increase in revenue for several customer businesses that have done micro-financing at Bank Syariah Indonesia KCP Sarolangun. Due to the lack of adequate and equitable direction to the customer's business, other factors cause the customer's income not to increase, namely the lack of human resources in financial reporting and lack of marketing knowledge.